2011
DOI: 10.1103/physrevb.84.054408
|View full text |Cite
|
Sign up to set email alerts
|

High-field magnetic phase transitions and spin excitations in magnetoelectric LiNiPO4

Abstract: The magnetically ordered phases and spin dynamics of magnetoelectric LiNiPO4 have been studied in fields up to 17.3 T along the c axis. Using neutron diffraction, we show that a previously proposed linearly polarized incommensurate (IC) structure exists only for temperatures just below the Néel temperature T N . The ordered IC structure at the lowest temperatures is shown instead to be an elliptically polarized canted spiral for fields larger than 12 T. The transition between the two IC phases is of second ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 22 publications
4
37
0
1
Order By: Relevance
“…The associated critical fields are in rough agreement with those reported in Ref 31. The two lowest transition fields at 12 and 16 T are in agreement with our previous studies 28, 30 . The ME response P x = α xz H z of the five phases is shown in Fig.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The associated critical fields are in rough agreement with those reported in Ref 31. The two lowest transition fields at 12 and 16 T are in agreement with our previous studies 28, 30 . The ME response P x = α xz H z of the five phases is shown in Fig.…”
Section: Resultssupporting
confidence: 81%
“…The pulse durations (FWHM) were 5 ms and 2 ms, respectively. The absolute value of the magnetization m was scaled to previous results obtained with static fields 30 . The electrical polarization was measured using a procedure similar to that described in Refs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the lithium-orthophosphates, it has been observed that the relative strength of the ME effect correlates with the effective total orbital moment with LiCoPO 4 (L = 3) and LiMnPO 4 (L = 0) displaying the largest and smallest ME coefficients [14][15][16][17] . Here, we report on the magnetic excitations of LiFePO 4 and expand on recent elastic and inelastic neutron studies of the lithium-orthophosphates [18][19][20] . Similar to other lithiumorthophosphates, LiFePO 4 possesses an intricate magnetic structure, where the Fe 2+ moments (S = 2; L = 2) order antiferromagnetically at T N = 50 K with moments pointing mainly along the b-direction 21,22 .…”
Section: Introductionmentioning
confidence: 99%